Genetic Analysis and Detection of fliCH1 and fliCH12 Genes Coding for Serologically Closely Related Flagellar Antigens in Human and Animal Pathogenic Escherichia coli - Beutin, Lothar; Delannoy, Sabine; Fach, Patrick (Frontiers in Microbiology, 2016)
The E. coli flagellar types H1 and H12 show a high serological cross-reactivity and molecular serotyping appears an advantageous method to establish a clear discrimination between these flagellar types. Analysis of fliCH1 and fliCH12 gene sequences showed that they were 97.5% identical at the nucleotide level. Because of this high degree of homology we developed a two-step real-time PCR detection procedure for reliable discrimination of H1 and H12 flagellar types in E. coli. In the first step, a real-time PCR assay for common detection of both fliCH1 and fliCH12 genes is used, followed in a second step by real-time PCR assays for specific detection of fliCH1 and fliCH12, respectively. The real-time PCR for common detection of fliCH1 and fliCH12 demonstrated 100% sensitivity and specificity as it reacted with all tested E. coli H1 and H12 strains and not with any of the reference strains encoding all the other 51 flagellar antigens. The fliCH1 and fliCH12 gene specific assays detected all E. coli H1 and all E. coli H12 strains, respectively (100% sensitivity). However, both assays showed cross-reactions with some flagellar type reference strains different from H1 and H12. The real-time PCR assays developed in this study can be used in combination for the detection and identification of E. coli H1 and H12 strains isolated from different sources.